POSTPARTUM DEPRESSION AND PERSONALITY - Andriani, Lela Dwi (Journal of Psychiatry Psychology and Behavioral Research, 2024)
Introduction – Postpartum depression is a psychological problem that occurs in women after giving birth. A study says that about 10-20% of women experience depression. The cause of postpartum depression is not known with certainty. Some studies say psychological factors are one of the causes, therefore researchers use Big Five Personality (conscientiousness, neuroticism, agreeableness, openness to experience, and extraversion) neuroticism, extraversion, conscientiousness, agreeableness, openness to experience) to help explain the description of personality types in postpartum mothers. This can help health workers in improving health services to mothers. This paper aims to find the relationship of personality with the degree of depression postpartum Methods – study, the source of data obtained from the electronic database used in this review literature uses 4 databases, namely Pubmed, Frontiers, ScienceDirect, and Elsevier which have been published from 2019-2022. Results – The results of this study neuroticism, extraversion, and conscientiousness have a significant association with the occurrence of postpartum depression. Discuss – Neuroticism personality type is also associated with anxiety in women after giving birth, therefore health workers need to learn personality types and conduct routine checks on postpartum mothers to minimize the occurrence of postpartum depression. Conclusion – In the Big Five Personalities personality types neuroticism, extraversion, and conscientiousness can be used as dominant indicators of the occurrence of postpartum depression, while for personality types agreeableness and openness to experience are currently still under further research development.  Keywords: personality, depression, postpartum